Straight synthesis of α and γ Alumina from Kaolin by HCl acid leaching - karimi, ebrahim; Bagherzadeh, Yasamin; Golmakani, Mohammad Hossein (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
In this work the preparation of alumina from kaolinite by leaching with hydrochloric acid is studied. Crude kaolin was calcined at 850°C and then leached with 6 M hydrochloric acid at 90°C. Aluminum hydroxide was precipitated by adding 6 M HCl solution to the leaching water. Finally, the precipitated aluminum hydroxide was heated at 1100°C and converted to aluminum oxide. The materials were identified by XRF, XRD and SEM-EDX techniques. alumina recovery The percentage of alumina recovery was determined at different kaolin particle sizes (–200 to –400 standard Tyler sieve ), different times (1, 2, 3 and 4 h), different leaching temperatures (80, 90, 100 and 104°C) and different concentrations of hydrochloric acid (20, 25, 30 and 37%). The phase changes of alumina were also investigated at two calcination temperatures (1100 and 1200°C). The purity of aluminum oxide obtained by this method is about 97% and the percentage of recovery is about 98%. It was observed that the kaolin granulation with dimensions smaller than 75 μm had no significant effect on the percentage of alumina recovery. It was also found that the percentage of alumina recovery increased with increasing leaching temperature.
Keywords: Alumina, Kaolin, Acid leaching, Hydrometallurgy, Hydrochloric acid